2002
DOI: 10.1002/pen.10949
|View full text |Cite
|
Sign up to set email alerts
|

Plasma surface treatments of melt‐extruded sheets of poly(L‐lactic acid)

Abstract: Poly(L‐lactic acid) sheets, prepared by melt extrusion, were treated with O2−, He−, and N2−plasmas generated in radio frequency (RF) at 13.56 MHz. Atmospheric pressure discharge at 20 kHz in helium was also applied to the modification of the sheets. The surface of the PLLA sheets was etched to form the characteristic morphology, and the patterns were different depending on the type of plasma. Polar groups composed of –COOH and –OH were incorporated by plasma treatment, and the surface became wettable. Surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
5
32
1
1
Order By: Relevance
“…However, as can be observed in Table 2, helium and plasma treatments add a large amount of nitrogen atoms to the PLA surfaces: helium plasma-treated PLA foils contain 2.7% nitrogen, while nitrogen plasma-treated PLA films contain 6.3% nitrogen. Hirotsu et al [39]. and Inagaki et al [11] found a water contact angle of approximately 55°and 50°after oxygen and argon plasma treatment respectively due to the incorporation of oxygen groups, which is in agreement with the results obtained in this work.…”
Section: Plasma Treatment: Contact Angle Measurements and Xps Analysissupporting
confidence: 94%
“…However, as can be observed in Table 2, helium and plasma treatments add a large amount of nitrogen atoms to the PLA surfaces: helium plasma-treated PLA foils contain 2.7% nitrogen, while nitrogen plasma-treated PLA films contain 6.3% nitrogen. Hirotsu et al [39]. and Inagaki et al [11] found a water contact angle of approximately 55°and 50°after oxygen and argon plasma treatment respectively due to the incorporation of oxygen groups, which is in agreement with the results obtained in this work.…”
Section: Plasma Treatment: Contact Angle Measurements and Xps Analysissupporting
confidence: 94%
“…From high-resolution XPS scans, the authors have concluded that after plasma treatment in air, the concentration of C-O and O-C=O groups increases, while the C-C and C-H functional groups decrease. Hirtosu et al observed a gradual increase in water contact angle when PLA samples were kept in dry air (Hirotsu et al, 2002). A similar hydrophobic recovery has recently been examined in detail by Morent et al, who employed a medium pressure DBD in different atmospheres for the surface modification of PLA.…”
Section: Plasma Treatment Of Biodegradable Polymersmentioning
confidence: 71%
“…Hirotsu et al published in 1997 one of the first studies on plasma modification of biodegradable polymers and treated PLA fabrics with a low pressure radio frequent (RF) discharge generated in pure oxygen and nitrogen (Hirotsu et al, 1997). The same group reported in 2002 about an enhancement of the wettability of PLLA sheets and showed a strong decrease in water contact angle from 80° to approximately 55° after 30 seconds of oxygen and helium plasma treatment (Hirotsu et al, 2002). They suggested that this increased wettability was only due to chemical changes of the surface, since pronounced etching is not likely to happen after such short treatment times.…”
Section: Examples Of Plasma-assisted Surface Modification Of Biodegramentioning
confidence: 94%
“…Plasma treatment did not have any significant influence on the water vapor permeability of PLA, however, since the bulk structure controlling the transport properties are unaffected by the treatment. Other types of plasmas such as oxygen, helium, and nitrogen plasmas have also been investigated (Hirotsu et al, 2002).…”
Section: Plasma Treatmentmentioning
confidence: 99%